2013
DOI: 10.1080/0951192x.2013.799784
|View full text |Cite
|
Sign up to set email alerts
|

Definition and recognition of rib features in aircraft structural part

Abstract: In this research, a new type of manufacturing feature that is commonly observed in aircraft structural parts, known as ribs, is defined and implemented using the object-oriented software engineering approach. The rib feature type is defined as a set of constrained and adjacent faces of a part which are associated with a set of specific rib machining operations. Computerized numerical control (CNC) operation experience and the machining knowledge are leveraged by analysing typical geometry interactions when gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Among them, 'n' sub-ribs can form a complete rib. To compare the computational efficiency of the proposed method, the typical rib recognition method [25] is used here. It can be seen from Fig.…”
Section: Illustration Of the Efficiency Of Rib Recognition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 'n' sub-ribs can form a complete rib. To compare the computational efficiency of the proposed method, the typical rib recognition method [25] is used here. It can be seen from Fig.…”
Section: Illustration Of the Efficiency Of Rib Recognition Methodsmentioning
confidence: 99%
“…Later approaches are all following this theory. Li et al [24,25] utilized the seed face as a key to the recognition of rib-features, and then improved this method in which the rib feature was considered to be an object that had some particular attributes. It can be seen that these feature recognition methods are all based on heuristic rules which first recognize the sub-ribs and then combined to form a main rib-feature.…”
Section: Related Workmentioning
confidence: 99%
“…In dealing with dynamic information such as on-line machine tool performance and in-process inspection of machined parts related to machine tool maintenance, Li et al [40,41] reported pioneering investigation and experimental work in on-line monitoring and inspection system based on a new dynamic feature concept (as opposed to traditional static geometry-based feature definition) for modelling the dynamic real-life information to achieve timely and responsive machining control. In their dynamic feature model, the relationships between the interim states of a part (workpiece-in-progress) and associated machining characteristics and knowledge have been investigated and dynamic information linked to different interim features have been modelled and integrated.…”
Section: Dynamics Of Knowledgementioning
confidence: 99%
“…The on-line monitoring of machine tool performance and in-process inspection of machined parts should be linked to machine tool maintenance as well, especially. Li et al [16,17] reported an integrated on-line monitoring and inspection system based on an innovative dynamic feature concept as the basis for modelling dynamic production information to achieve accurate machining process control. In their dynamic feature model, the various relationships between the interim geometry of a part and associated machining characteristics have been investigated and dynamic information linked to different interim feature states have been represented.…”
Section: Previous Research In Computerised Maintenance Managementmentioning
confidence: 99%